If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 16m + -5(2m + -3) = 33 Reorder the terms: 16m + -5(-3 + 2m) = 33 16m + (-3 * -5 + 2m * -5) = 33 16m + (15 + -10m) = 33 Reorder the terms: 15 + 16m + -10m = 33 Combine like terms: 16m + -10m = 6m 15 + 6m = 33 Solving 15 + 6m = 33 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-15' to each side of the equation. 15 + -15 + 6m = 33 + -15 Combine like terms: 15 + -15 = 0 0 + 6m = 33 + -15 6m = 33 + -15 Combine like terms: 33 + -15 = 18 6m = 18 Divide each side by '6'. m = 3 Simplifying m = 3
| 1.5(x+5)=-(3x+15) | | 6y-15=19y | | 7=7(2-4) | | c+11=11c-19 | | X(2x+8)=3x-4 | | 69.4/4 | | 4km2/12k | | 41s-6=38s | | 24b-36=6b | | 0=9w^2-30w+25 | | X(2x+8)=(3x-4) | | 3x-8=44-X | | 8y-11=6y+7 | | 4(2k+1)-18=26 | | 24/x=16 | | 15y+12=11y+20 | | 2cos^2x-sinx-1=0 | | 12(v+4)-3v=3(3v+3)-18 | | 0=4u^2-15u-4 | | 16q-10=14q | | 1/2x-2=2x-1/2 | | 15m+8=10m-7 | | 2p-14=p+16 | | c-3=2c-12 | | -8t=4t+5+2t | | 7.8×9/4 | | 18v=14v+16 | | 1/3x4= | | -10(x)=5-10x | | 6q=10q-16 | | 7=7(5-4) | | 5v-8v-3v-6= |